# Prove the following identities csc^2 x / cos^2 x = sec^2 x csc^2 x (sin x / 1-cotx) + cosx/1-tanx = sinx + cosx

### 1 Answer | Add Yours

1) L.H.S.=`(csc^2 x) / (cos^2 x)=(csc^2 x)*1 / (cos^2 x)`

Since, `1/cos^2 x=sec^2 x` So,

L.H.S.=`sec^2 x* csc^2 x` =R.H.S.

**Hence, the proof.**

2) L.H.S.=`(sin x) / (1-cotx) + (cosx)/(1-tanx)`

`=sinx/ (1-cosx/sinx) + (cosx)/(1-sinx/cosx)`

`=sinx/ ((sinx-cosx)/sinx) + (cosx)/((cosx-sinx)/cosx)`

`=(sin^2x)/ (sinx-cosx) - (cos^2x)/(sinx-cosx)`

`=((sinx-cosx)(sinx+cosx))/(sinx-cosx)`

`=sinx+cosx` =R.H.S.

**Hence, the proof.**

**Sources:**